The aged hematopoietic system promotes hippocampal‐dependent cognitive decline. Issue 8 (21st July 2020) - Smith, Lucas K.; Verovskaya, Evgenia; Bieri, Gregor; Horowitz, Alana M.; von Ungern‐Sternberg, Saskia N. I.; Lin, Karin; Seizer, Peter; Passegué, Emmanuelle; Villeda, Saul A.
Abstract: The aged systemic milieu promotes cellular and cognitive impairments in the hippocampus. Here, we report that aging of the hematopoietic system directly contributes to the pro‐aging effects of old blood on cognition. Using a heterochronic hematopoietic stem cell (HSC) transplantation model (in which the blood of young mice is reconstituted with old HSCs), we find that exposure to an old hematopoietic system inhibits hippocampal neurogenesis, decreases synaptic marker expression, and impairs cognition. We identify a number of factors elevated in the blood of young mice reconstituted with old HSCs, of which cyclophilin A (CyPA) acts as a pro‐aging factor. Increased systemic levels of CyPA impair cognition in young mice, while inhibition of CyPA in aged mice improves cognition. Together, these data identify age‐related changes in the hematopoietic system as drivers of hippocampal aging. Abstract : The aged systemic milieu promotes cellular and cognitive impairments in the hippocampus. Here, we report that heterochronic hematopoietic stem cell (HSC) transplantation impairs hippocampal neurogenesis, decreases synaptic marker expression, and elicits age‐related cognitive impairments in young mice. We identify a number of factors that are elevated in the blood of young mice reconstituted with old HSCs, of which cyclophilin A (CyPA) acts as a pro‐aging factor. Increased systemic levels of CyPA impair cognition in young mice, while inhibition of CyPA in aged mice improves cognition.